2001
DOI: 10.1007/s004310100849
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound measurements of bone speed of sound in premature infants

Abstract: The results indicate that tibial speed of sound was reduced in premature infants (in particular very low birth weight) compared to full-term infants even when premature infants reached the corrected age of their full-term peers. The potential role of this technique in assessing osteopenia in premature infants warrants further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
58
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 16 publications
9
58
0
2
Order By: Relevance
“…39 Although urinary excretion of calcium and phosphate were not related to QUS in our study, AP correlated inversely with QUS, which confirms reports applying both QUS and DXA that found AP to predict reduced bone density with a sensitivity of 88% and a specificity of 71%. 14,15,40,41 The lack of correlation between AP or QUS and serum levels of calcium or phosphate in our patients is most likely due to the stringent regulation of these two minerals by a complex endocrine system to keep their serum levelFessential for many organ functionsFwithin normal limits. As expected, several risk factors for reduced bone formation showed a relevant influence on QUS, that is, the duration of parenteral nutrition or mechanical ventilation and the treatment with diuretics or corticosteroids.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…39 Although urinary excretion of calcium and phosphate were not related to QUS in our study, AP correlated inversely with QUS, which confirms reports applying both QUS and DXA that found AP to predict reduced bone density with a sensitivity of 88% and a specificity of 71%. 14,15,40,41 The lack of correlation between AP or QUS and serum levels of calcium or phosphate in our patients is most likely due to the stringent regulation of these two minerals by a complex endocrine system to keep their serum levelFessential for many organ functionsFwithin normal limits. As expected, several risk factors for reduced bone formation showed a relevant influence on QUS, that is, the duration of parenteral nutrition or mechanical ventilation and the treatment with diuretics or corticosteroids.…”
Section: Discussionmentioning
confidence: 79%
“…Our data also confirm previous studies that reported a correlation of bone quality with gestational age and birth weight both by DXA [23][24][25][26] and QUS. [9][10][11][12][13][14][15]27,28 Multivariate analysis confirmed postconceptional age as the most relevant predictor of bone quality. Body weight was the strongest predictor of QUS in the most immature infants but lost its significance in term neonates.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Since then, a quantitative ultrasound instrument has been developed and marketed, that allows measuring bone SOS in small infants on a routine basis. 6 Using this instrument, we have recently developed standard curves of neonatal bone SOS in appropriately grown, singleton infants ranging in gestational age from 25 to 42 weeks. 7 We designed this study in order to measure the ultrasound bone velocity of LGA InDMs.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The two methods can yield divergent results. Studies that used either DEXA [13][14][15][16][17] or tibial QUS [18][19][20][21] report lower indices of bone strength and mineral content in preterm infants versus infants born at term. However, studies that used DEXA or tibial QUS to compare bone status of SGA versus AGA newborn infants yield different results.…”
Section: Introductionmentioning
confidence: 99%